Fetomaternal Outcome in Eclampsia at Tertiary Care Centre: A Descriptive Cross-Sectional Study - Shah, Ravi Kumar; Ansari, Sana; Mushtaq, Rehana; Shrestha, Ruby; Shah, Pravin; Jaiswal, Arushi; Deep, Jagat Prasad (Med Phoenix, 2023)
Introduction: Eclampsia is a life threatening emergency condition that remains a leading cause of maternal and perinatal mortality. It is one of the causes of preventable maternal mortality. There are specific risks for the mother as this condition lead to seizure and may cause woman to lose consciousness and if the fetus is not delivered, this condition can cause the death of the mother and or the fetus. This study was conducted to evaluate the fetomaternal outcome in eclampsia. Materials and Methods: This is a descriptive cross sectional study done at National Medical College Teaching Hospital from 1st February 2021 to 31st January 2022. Ethical approval was obtained from IRC (regd no. F-NMC/518/076-77). During the study period 1496 women delivered. Out of this, 44 patients with generalized tonic-clonic convulsions during pregnancy / labour / within 7 days of delivery were included in the study criteria. The data analyzed included various maternal parameters, fetal parameters and pregnancy outcomes. Result: Among 1496, 44 patients (2.94%) developed eclampsia, 38.63% in age group of < 20 years, 59.09% were primigravida, 84.09% unbooked, 63.63% presented with antepartum eclampsia, delivered by caesarean 63.63%. There was 2.26% maternal mortality due to cerebrovascular accident. Perinatal mortality was 11.36% which included stillbirth 6.81%nand neonatal death 4.54%. Conclusion: Regular antenatal checkup, early detection of disease, timely referral, and early initiation and treatment in patients with eclampsia improve outcomes. Treatment of these patients should be carried out in tertiary care centers where intensive care units, NICU facilities, and multidisciplinary units are available.